Systematic Review: The Effectiveness of Resveratrol in Inhibiting Colorectal Cancer Cell Proliferation - Muh. Rifai B; Rachmat Faisal Syamsu; Salahuddin Andi Palloge (Journal La Medihealtico, 2025)
Colorectal cancer is one of the leading causes of cancer-related morbidity and mortality worldwide, with increasing incidence particularly in developing countries. Conventional treatments face challenges such as resistance and toxicity. Resveratrol, a natural polyphenol found in grapes, peanuts, and berries, has been reported to exert antioxidant, anti-inflammatory, and anticancer effects. To systematically evaluate the effects of resveratrol on parameters related to colorectal cancer in experimental animal models. Method: A qualitative systematic review was conducted by searching PubMed, Scopus, Sinta, and Google Scholar for studies published between 2020 and 2025. Inclusion criteria were in vivo studies using animal models of colorectal cancer, with resveratrol as the sole intervention, and reporting at least one parameter such as apoptosis, cell proliferation, oxidative stress, or inflammatory markers. Studies in vitro, in humans, or with combined interventions were excluded. A total of 512 articles were initially identified. After screening and applying eligibility criteria, seven studies were included. The findings consistently demonstrated that resveratrol suppressed tumor initiation and progression via multiple mechanisms: inhibition of Wnt/β-catenin signaling, induction of apoptosis and autophagy through FOXQ1 inhibition, reduction of oxidative stress and DNA damage, suppression of NF-κB signaling, and inhibition of epithelial mesenchymal transition and angiogenesis. Furthermore, resveratrol reduced tumor burden, metastasis, and inflammation in various colorectal cancer models. Resveratrol exhibits significant chemopreventive and therapeutic potential against colorectal cancer through pleiotropic mechanisms targeting proliferation, apoptosis, oxidative stress, and inflammation. These findings support resveratrol as a promising candidate for adjunctive therapy, although further clinical studies are required to confirm efficacy and safety in humans.